Production and characterization of gelatin from the collagen of chicken feet. - Andrada, Marvelous Grace Sabino (2016.)
The demand for gelatin continuously increases for food and pharmaceutical applications. Chicken feet, a low-valued by-product of the poultry industry is known as a source of gelatin. This paper investigated the production of protein-rich gelatin through the extraction of collagen from chicken feet. In a 2 x 2 factorial experiment, the yield and properties of collagen were determined using two types of organic acids (4% acetic and 5% citric) and at two soaking times (16 h and 36 h). Two-way ANOVA at 5% confidence level showed that only the type of acid significantly affected the extraction of collagen with 5% citric acid yielding 23.91% and 24.29% at 16 h and 36 g soaking, respectively. However, the 4% acetic acid was significantly higher than 5% citric acid in terms of protein content in w/v dried basics (80.50% at 16 h and 79.56% at 36 h); and viscocity (36.00 Pa-s at 16 h and 32.63 Pa-s at 36 h). The pH of collagen from both extracants and two seeking times were within the accepted range of pH (2.46 - 3.24) based on GMIA. A brighter yellow color of collagen from all treatments was observed at 36 h of soaking. Gelatin was produced by denaturing collagen through heating at 60° C for 30 minutes. Only the time of soaking significantly affected the gelatin yield with 36 h resulting to higher yield than 16 h. Although not significantly different, the highest yield of chicken feet gelatin (74.54%) was obtained with 5% citric acid compared to 71.17% with acetic acid. Gelatin processed from 5% citric acid for 16 h was ranked as the Most Preferred by panel of evaluators. All treatments were rated ?like slightly? except for the treatment in 4% acetic acid for 36 h which was ?disliked very much? due to sourness. The gel strength were within the range of 50-300 Bloom, classified as ?low bloom? and is considered a good quality gelatin according to GMIA. The protein content of gelatin from 4% acetic acid was significantly higher (73.58% at 16 h and 78.11 at 36 h) than from 5% citric acid (65.21% at 16 h and 65.11% at 36 h). This study showed that gelatin from chicken feet collagen was slightly acceptable but with its high protein content and gel strength it has potential for use in food applications.
Thesis - B.S. (Food Technology) - School of Technology, University of the Philippines Visayas.
Keywords: Gelatin; Collagen -- chicken feet